(untitled) (Lectio: Journal of Language and Language Teaching, 2025)
Generation Z (Gen Z), the dominant media consumer, actively seeks relatability, yet the specific speaking styles that foster this connection remain unidentified, creating a gap between media production and reception studies. This descriptive qualitative study analyzed semi-structured in-depth interviews with 31 Gen Z informants through a constructivist lens. The findings confirm Gen Z are active "meaning navigators," aligning with Uses and Gratifications (U&G) theory. Relatability is not a singular concept but a spectrum fulfilling distinct needs: (1) a "Safe Space" (emotional-reflective), (2) a "Virtual Hangout Friend" (social-communal), and (3) a "Mentor" (aspirational-intellectual). Crucially, each dimension is underpinned by specific speaking styles, from "gentle and empathetic" to "spontaneous and outspoken" or "structured and logical." The most significant finding is the presence of "skill transfer," as Gen Z consciously or unconsciously adopts these admired styles. The study concludes that passive media consumption, when driven by strong relatability, functions as a powerful implicit learning process, with Gen Z actively selecting virtual mentors to shape their real-world communicative identities.